MENINGKATKAN KETERAMPILAN GURU PAUD DALAM MENANGANI ANAK BERKEBUTUHAN KHUSUS (ABK) DI PAUD - rafikayati, ana; badiah, lutfi isni; mudhar, mudhar (LPPM Universitas PGRI Adi Buana Surabaya, 2019)
The purpose of identifying and assessing children with special needs training is to improve: 1) early childhood teacher’s knowledge about types of special needs children, 2) skills of early childhood teacher in identifying special needs children, and 3) skills of early childhood teacher in assessing special needs children. This activity was attended by 20 early childhood teacher from Peek A Boo School and Permata Bunda Schools in Sidoarjo. The methods used in training activities are lectures, group discussions, and practices. The results of this activity were obtained that after attending the training: 1) there was an increase in the knowledge of early childhood teacher regarding the types of children with special needs from 65% to 90%, 2) The skills of teachers in identifying also increased, from 10% to 55% able to identify children with special needs , and 3) an increase in assessment activities of children with special needs, from 10% to 50%. Thus, this training can effectively increase the knowledge and adequacy of early childhood teacher to identification and assessment activities of children with special needs.